Abonamiento foliar del Pennisetum sp. “maralfalfa” y su efecto en el rendimiento del forraje, Zungarococha – Loreto. 2021 - Castro Lopez, Katheryn Alondra (2022)
The present investigation was carried out at the National University of the Peruvian Amazon in the Faculty of Agronomy in the Cattle Project in the Fundo de Zungarococha, entitled FOLIAR FERTILIZING OF Pennisetum sp. “MARALFALFA” AND ITS EFFECT ON FORAGE YIELD, ZUNGAROCOCHA – LORETO. 2021”. The evaluations were carried out at the ninth week after planting with vegetative seed (bushes), in plots of 3.0 m x 1.2 m and an experimental area of 141.1 m2. With a Random Complete Block Design (D.B.C.A) design, with four treatments and four repetitions, the following results were achieved: Regarding the agronomic characteristics such as plant height, 1.57 m was obtained, green matter 2.60 kg/m2, dry matter of 0.54 kg/m2 and coverage of 92.20%, with the T3 treatment (60% of the biofertilizer) in the forage Pennisetum sp, "Maralfalfa" at 60 days. It is observed that in this same T3 treatment (60% of the biofertilizer ) in the forage Pennisetum sp, "Maralfalfa" at 60 days, a yield of 26,000 kilos/ha was achieved, reaching the following conclusions that the analysis of variance does not express statistical difference for blocks and if a high significance between biofertilizer concentration treatments, this indicates that the higher the concentration of the Pennisetum sp "Maralfalfa" forage, it takes advantage of the macro and micronutrients for the nutrition of the most important organs of the plant, such as the roots and leaves. as for its growth and development which is expressed in the dependent variables.